A comparative assessment of two rooftop hybrid energy systems in an Ecuadorian academic complex - Ruben Hidalgo-Leon; Jaqueline Litardo; Scarleth Vasconcelos; Frank Porras; Miguel Torres; Christopher Varela; Jorge Vega; Vicente Macas-Espinosa; Pritpal Singh; Guillermo Soriano (Results in Engineering)
This paper presents the optimal design and economic viability of two rooftop hybrid energy systems intended for an academic complex: a grid-connected system and a standalone configuration. The goal is to reduce or eliminate the complex’s reliance on conventional electricity through renewable energy integration focused on fuel cell (FC) technology. The systems include photovoltaic (PV) modules, FCs, electrolyzers, converters, H2 storage tanks, a battery energy storage system (BESS), and a grid connection. Simulations were conducted using Homer Pro, leveraging detailed hourly meteorological and load data. The optimization considered techno-economic criteria to satisfy a demand of 123,649 kWh/year, providing a reproducible and data-driven framework applicable to similar academic facilities. Results indicate that the grid-connected system achieved a 75.63 % renewable fraction, with an optimized configuration of 120 kWp PV, 100 kW converter, 8 kW FC, 50 kW electrolyzer, and a 20 kg H₂ tank. The system delivered average outputs of 13,296 kWh/month PV and 2868.61 kWh/month FC, with 56 % of renewable energy feeding the electrolyzer. The standalone system required larger capacities—180 kWp PV, 32 kW FC, 120 kW electrolyzer, 100 kg H₂ tank, and 192 kWh BESS—and produced 239,335.64 kWh/year from PV and 40,570.74 kWh/year from FCs. H2 production reached 1936 kg/year and 2276 kg/year in the grid-connected and standalone systems, respectively. In addition, net present costs over 25 years were USD 491,519.71 and USD 1079,532.58. This study presents a first-time analysis of H2-based rooftop systems for this university, offering useful guidance for its energy transition.